Self-actualization of KIP Scholarship Recipient Students / Aktualisasi Diri Mahasiswa Penerima Beasiswa Kartu Indonesia Pintar - Fadhilah, Sinta Rahmatil; Sanjaya, Nur Aeni; Aminah, Siti; Saputra, Donal; Nurdiani, Putri (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
Students are helped financially by scholarships provided by the government, universities or other institutions. The scholarships received by students are able to make them more independent and free to be creative, there is satisfaction and a sense of pride present in the students who receive these scholarships. So this research aims to explore the self-actualization of students who receive the Smart Indonesia Card scholarship. This research is expected to provide insight into the factors that influence the self-actualization process, as well as support from various parties, including educational institutions and the government. This type of research is qualitative research with data collection techniques of unstructured interviews and non-participant observation. Informants in this study were selected using snowball sampling techniques. The informants in this research were students who received Smart Indonesia Card scholarships at UIN Sulthan Thaha Saifuddin Jambi and UIN Antasari Banjarmasin. The results of this research show that the Smart Indonesia Card scholarship is able to meet students' basic needs. By fulfilling these basic needs, students are able to actualize themselves. The description of self-actualization possessed by students who receive Smart Indonesia Card scholarships at UIN Sulthan Thaha Saifuddin Jambi and UIN Antasari Banjarmasin includes feeling happy, more creative, better able to maximize potential, self-confident, independent and prosocial.